Critical Success Factors of Total Quality Management Implementation in a Custom-made Furniture Manufacturing Company - Ahmad @ Mohamad, Md Fauzi; Ying Xian, Yoong; Rashid, Nurulizwa; binti Abdul Latip, Hamrila (Research in Management of Technology and Business, 2023)
The market demands for product quality improvement have increased, and the Total Quality Management (TQM) approach has proven effective in enhancing product quality. Implementing TQM can be instrumental in achieving an organization's growth and success in the global and local furniture markets. In this competitive business environment, furniture companies must deliver high-quality products and add value to their customers consistently. This study was conducted with the purpose to determine the critical success factor of TQM implementation in a custom-made furniture manufacturing company in which ABC company was selected as the case study. According to the study, the factors includes management commitment and leadership, employee involvement, total customer satisfaction, continuous improvement, training, communication and teamwork. The data shown that management commitment and leadership factor was ranked first in terms of its importance to the successful implementation of TQM. Apart from that, several barriers faced by the company was identified during implementation of TQM. A SWOT analysis based on the TQM implementation is being discussed according to the interviews with five employees of the company. Therefore, this study enables further understanding on how to implement TQM into company practice successfully and the challenges that faced by the company during implementation TQM.